Ethiopia. The Boran cattle and their tribal owners - Alberro, M. (1986)
The Boran cattle, indigenous to southern Ethiopia, at one time formed the basis of a thriving slaughter stock trade between Ethiopia and East Africa. Ranchers in Kenya buying these cattle as they moved down to urban centers for slaughter found that they were more productive under the adverse environmental conditions than the pure or crossbred European exotic cattle with which they had originally stocked the ranches. In 1951 a Kenyan Boran cattle breeders’ society was established, the second such society in Africa. At present time the Borana area, like other areas of Africa, is suffering from one of the worst droughts in history. The Borona pastoralists have lost at least 40 percent of their fertile cows, and as a result their social and economic conditions have deteriorated.